Keragaman Genetik Dalam Galur dan Heritabilitas Galur-Galur S4 Tanaman Jagung (Zea mays L.) pada Kondisi Normal di lahan Kering - Rachman, Gina Juniarti; Sudika, I Wayan; Suliartini, Ni Wayan Sri (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to determine the genetic diversity of each S4 line for leaf angle characters, harvest age and dry kernel weight per planting (yield) of corn plants under normal conditions on dry land and to determine the heritability value in the broad sense of quantitative characters of the S4 line of corn plants on dry land. The experimental design used was a non-factorial Randomized Block Design (RAK), with treatment of 16 genotypes, namely 15 S4 lines and 1 NK212 hybrid line. Each treatment was repeated 2 times to obtain 32 experimental units. Characters observed included plant height, number of leaves, stem diameter, leaf area, leaf angle, harvest age, ear length, ear diameter, harvested dry ear weight, weight of 1,000 seeds, and dry shelled seed weight per plant (Yield). Uniformity of the three quantitative characters, namely leaf angle, harvest age and dry seed weight per planting (Yield) is the basis for determining a line as a pure line. The line that has a uniform category of genetic diversity was obtained in the S4.10 line. Heritability values with low criteria were found in the characters number of leaves, leaf angle, ear length, ear diameter and dry kernel weight (Yield). Characters with moderate heritability values were found in plant height, stem diameter, leaf area, harvest dry ear weight and 1000 seed weight.